ANALISIS MINAT MASYARAKAT KABUPATEN MANDAILING NATAL TERHADAP JASA DAN FASILITAS LEMBAGA ASURANSI (Studi Kasus Pegawai Negeri Sipil) - As’at Nasution; Irsyad Lubis (Ekonomi dan Keuangan, 2015)
This research aimed to analyses of proclivity of Mandailing Natal regency people to the insurance agency cervices and facilities such as knowledge of the insurance, proclivity to the insurance and insurance contraintsto the people. The data in this research use primary data by giving questionnaire to 100 civil servants in Mandailing Natal as respondents. The answer of the respondents are used to know condition of proclivity of Mandailing Natal regency people to the insurance agency service and facilities. The analyses that is used descriptive qualitative analyses. The technique of analyses data. In order to data tabulation, frequensi distribution and presentation also.The result show that the level of knowledge of insurance is relatively satisfy, while the proclivity of people to take out insurance is low because the insurance company off erring their product to the people is less. From the result of the research is able to know the insuransi marketing is low due to lack. To people cause people of proctivity are less to join in the insurance. From the result of this research is that the constraints face by the people. Due to lack of comprehension on the explanation and the languge that is used by the insurance company.Keywords: People, Insurance, Civil Servants